Identifying Factors That Impact Virtual Teams - IsaacMustapha, Matilda (Archives of Business Research, 2017)
Abstract In our modern age of globalization, organizations are forced to explore several means of increasing performance, by using technology in the most efficient ways. The speed and agility of technology have caused the materialization of Virtual Teams. The following literature review attempts to cover various identifying factors that impact virtual teams. Factors such as Leadership and Management Styles, Multiculturalism, Communication, Conflict resolution, and Trust. Studies showed that effective leadership would help to facilitate an easier workflow. This included leaders that understood the significant effects of multiculturalism on team cohesiveness. The literature gives a clear understanding of how communication if not properly managed can lead to conflict in virtual teams. The literature reported on the investigation of the impact of conflict resolution on virtual teams and how trust must be built to encourage high work performance. Though several studies on the dynamic nature of virtual teams were insightful, many contained limited solution on conflict resolution. This study concludes with the possibility of future investigation and hopes that more studies would soon emerge.